The correct answer is:
y=3x-4
Using the graph, derive the equation of the line in slope-intercept form.
(1 point)
Responses
y=−3x−4
y equals negative 3 x minus 4
y=3x+4
y equals 3 x plus 4
y=3x−4
y equals 3 x minus 4
3x−y=4
7 answers
wrong
I apologize for the incorrect response. Please provide me with more information or the graph itself so that I can accurately derive the equation of the line in slope-intercept form.
Use the image to answer the question.
An illustration of a coordinate plane with four quadrants shows the x-axis ranging from negative 9 to 9 and the y-axis ranging from negative 11 to 11 in increments of 1. A solid upward line with arrows at both ends is plotted on the graph. The line passes through the plotted points left parenthesis 0 comma 4 right parenthesis and left parenthesis 1 comma 8 right parenthesis.
Derive the equation of the line in slope-intercept form.
(1 point)
An illustration of a coordinate plane with four quadrants shows the x-axis ranging from negative 9 to 9 and the y-axis ranging from negative 11 to 11 in increments of 1. A solid upward line with arrows at both ends is plotted on the graph. The line passes through the plotted points left parenthesis 0 comma 4 right parenthesis and left parenthesis 1 comma 8 right parenthesis.
Derive the equation of the line in slope-intercept form.
(1 point)
To derive the equation of the line in slope-intercept form, we need to find the slope of the line and the y-intercept.
The slope of a line can be calculated using the formula:
slope (m) = (change in y) / (change in x)
Given that the line passes through the points (0, 4) and (1, 8):
change in y = 8 - 4 = 4
change in x = 1 - 0 = 1
slope (m) = 4/1 = 4
Now that we have the slope, we can use the point-slope form of a linear equation to find the y-intercept (b):
y - y1 = m(x - x1)
Using the point (0, 4):
y - 4 = 4(x - 0)
y - 4 = 4x
To write it in slope-intercept form (y = mx + b), we isolate the y variable:
y = 4x + 4
Therefore, the equation of the line in slope-intercept form is:
y = 4x + 4.
The slope of a line can be calculated using the formula:
slope (m) = (change in y) / (change in x)
Given that the line passes through the points (0, 4) and (1, 8):
change in y = 8 - 4 = 4
change in x = 1 - 0 = 1
slope (m) = 4/1 = 4
Now that we have the slope, we can use the point-slope form of a linear equation to find the y-intercept (b):
y - y1 = m(x - x1)
Using the point (0, 4):
y - 4 = 4(x - 0)
y - 4 = 4x
To write it in slope-intercept form (y = mx + b), we isolate the y variable:
y = 4x + 4
Therefore, the equation of the line in slope-intercept form is:
y = 4x + 4.
kappa i can tell you got a bad grade
I apologize if my previous response was not clear or satisfactory. Here is the correct way to derive the equation of the line in slope-intercept form.
Given that the line passes through the points (0, 4) and (1, 8), we can find the slope of the line using the formula:
slope (m) = (change in y) / (change in x)
change in y = 8 - 4 = 4
change in x = 1 - 0 = 1
slope (m) = 4/1 = 4
Now that we have the slope, we can use the point-slope form of a linear equation to find the equation of the line:
y - y1 = m(x - x1)
Using the point (0, 4):
y - 4 = 4(x - 0)
Simplifying:
y - 4 = 4x
To write it in slope-intercept form (y = mx + b), we isolate the y variable:
y = 4x + 4
Therefore, the equation of the line in slope-intercept form is:
y = 4x + 4.
I apologize for any confusion in my previous response. Let me know if there is anything else I can assist you with.
Given that the line passes through the points (0, 4) and (1, 8), we can find the slope of the line using the formula:
slope (m) = (change in y) / (change in x)
change in y = 8 - 4 = 4
change in x = 1 - 0 = 1
slope (m) = 4/1 = 4
Now that we have the slope, we can use the point-slope form of a linear equation to find the equation of the line:
y - y1 = m(x - x1)
Using the point (0, 4):
y - 4 = 4(x - 0)
Simplifying:
y - 4 = 4x
To write it in slope-intercept form (y = mx + b), we isolate the y variable:
y = 4x + 4
Therefore, the equation of the line in slope-intercept form is:
y = 4x + 4.
I apologize for any confusion in my previous response. Let me know if there is anything else I can assist you with.